Prospective Study of the Recovery of CD4+ T cell Subsets and Their Relationship to the Overall Survival Following Allogeneic Hematopoietic Stem Cell Transplantation - Eida Elmansorry, (AlQalam Journal of Medical and Applied Sciences, 2024)
The immune recovery (IR) following the allogeneic hematopoietic stem cell transplantation (allo-HSCT) is an advancement procedure that fundamentally correlated to the curative success. It is critical to understand the interfering factors in IR to prevent the HSCT-related mortality. The factors influencing CD4+T cell recovery post (HSCT) are not well totally characterized. This work was conducted to analyze the kinetics of CD4+T cell subsets recovery post HSCT, and to correlate their reconstitution with different factors that may influence the overall survival following HSCT. We prospectively evaluated the clinical outcomes and CD4+ T lymphocyte subtypes regeneration kinetics at different time-points of 22 patients with allogeneic HSCT for malignant and non-malignant diseases from 2007 to 2008. Statistics (means, minimal, and maximal values) were used to describe patient baseline characteristics. Results were presented as absolute count of CD4+ T cells, % of naive and memory subsets, and p-values. Thymus-independent pathways were responsible for the rapid recovery of memory CD4+T cells less than 6 months after HSCT. Thymus-dependent pathways were activated between 6 and 12 months in the majority of patients with increasing counts of naive CD4+ T cell. Furthermore, increasing patient age and chronic GVHD predicted the slow naive T cell recovery and also predicted high memory T cell numbers. The proper CD4 + reconstitution was associated with younger age, a non-malignant disease and a lower incidence of acute graft-versus-host disease ≥ grade 2. Additionally, the CD4+ T lymphocytes recovery ≥ 200/µl was associated with a higher overall survival. Different factors affected the IR post the allo-HSCT. The CD4+ count ≥ 200/µl was a simple IR predictor of overall survival and better clinical outcome following allogeneic HSCT. إن التعافي المناعي بعد عملية زرع الخلايا الخيفية الجذعية الدموية هو إجراء متطور يرتبط ارتباطًا أساسيًا بنجاح العلاج. من الأهمية بمكان فهم العوامل المتداخلة في التعافي المناعي لمنع الوفيات المرتبطة بعملية زرع الخلايا الخيفية الجذعية الدموية. العوامل التي تؤثر على تعافي الخلايا التائية الحاملة للمستقبل سي دي 4 بعد عملية زرع الخلايا الخيفية الجذعية الدموية ليست محددة تمامًا. تم إجراء هذا العمل استباقيا لتحليل حركية تعافي مجموعات الخلايا التائية الحاملة للمستقبل سي دي4 بعد عملية زرع الخلايا الخيفية الجذعية الدموية ، وربط إعادة تكوينها بعوامل مختلفة قد تؤثر على البقاء الإجمالي بعد عملية زرع الخلايا الخيفية الجذعية الدموية. لقد قمنا بتقييم النتائج السريرية وحركية تجديد الخلايا التائية الحاملة للمستقبل سي دي4 في نقاط زمنية مختلفة لـ 22 مريضًا خضعوا لزراعة الخلايا الجذعية المكونة للدم من النوع الخيفي لأمراض خبيثة وغير خبيثة من عام 2007 إلى عام 2008. تم استخدام الإحصائيات (المتوسطات والقيم الدنيا والقصوى) لوصف خصائص خط الأساس للمريض. تم تقديم النتائج على أنها عدد مطلق للخلايا التائية الحاملة للمستقبل سي دي4 ونسبة الخلايا الساذجة والذاكرة وقيم p. كانت المسارات المستقلة عن الغدة الزعترية مسؤولة عن التعافي السريع لخلايا الذاكرة التائية الحاملة للمستقبل سي دي4 بعد أقل من 6 أشهر من زراعة الخلايا الجذعية المكونة للدم. تم تنشيط المسارات المعتمدة على الغدة الزعترية بين 6 و 12 شهرًا في غالبية المرضى مع زيادة في عدد الخلايا التائية الحاملة للمستقبل سي دي4 الساذجة. علاوة على ذلك، فإن زيادة عمر المريض ومرض الزراعة ضد المضيف المزمن تنبأ بالتعافي البطيء للخلايا التائية الساذجة وتنبأ أيضًا بأعداد عالية من الخلايا التائية للذاكرة. ارتبطت الإعادة السليمة لتكوين الخلايا التائية الحاملة للمستقبل سي دي4 بالعمر الصغير والمرض غير الخبيث وانخفاض معدل الإصابة بمرض الزراعة ضد المضيف الحاد ≥ الدرجة 2. بالإضافة إلى ذلك، ارتبط تعافي الخلايا الليمفاوية التائية الحاملة للمستقبل سي دي 4بتركيز 200≤ ميكرو لتر ببقاء أعلى بشكل عام. أثرت عوامل مختلفة على التعافي المناعي بعد زراعة الخلايا الجذعية المكونة للدم. كان عدد خلايا التائية الحاملة للمستقبل سي دي 4بتركيز 200≤ ميكرو لتر مؤشرًا بسيطًا للتنبؤ بالبقاء على قيد الحياة بشكل عام والنتائج السريرية الأفضل بعد زراعة الخلايا الجذعية المكونة للدم من الخلايا الجذعية المتماثلة